Psicoterapia Humanista y Factores Psicológicos para la Ejecución Deportiva en atletas universitarios de alto rendimiento. Un estudio de caso - Nieto Payán, Aldo Orlando (Universidad Autónoma de Ciudad Juárez, 2019)
The objective of this research was to analyse how humanist psychotherapy influences the fundamental psychological factors for the sporting performance in high performance athletes of the Autonomous University of Ciudad Juárez. A case study was carried out with two participants of 18 and 25 years of a university athletic team in which the problems of their daily life that could affect their psychoemotional state and their sporting performance were individually attended. It was supported by documentary studies, on evaluations to groups of athletes before and after the psychological intervention. The psychological Inventory of sports Execution (IPED) of Hernández and Mendo (2006) was applied before and after the accompanying process. The results show an increase in the factors that make up the IPED. It is concluded that the process of humanist psychotherapy influences in a positive way the psychological factors fundamental for the sport execution in addition to the development of resources that favor their personal life.